RESPON PEMBERIAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffee robusta) - Syahruni Thamrin; Junaedi Junaedi; Irmayana Irmayana (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2020)
The study aims to determine the effect of various doses of NPK fertilizer on the growth of Robusta coffee plant seeds. The study was conducted at the screen house of the Department of Plantation Plant Cultivation at the Pangkep State Polytechnic of Agricultural. The study uses a simple statistical analysis with a Randomized Group Design (RBD) pattern, which is to calculate the mean (average) of each experiment, which consists of 3 levels of treatment, namely: without applying NPK fertilizer (P0), NPK fertilizer application with a dose of 14 grams (P1), application of NPK fertilizer at a dose of 18 grams (P2), and application of NPK fertilizer at a dose of 22 grams (P3). The results showed that NPK fertilizer application had no significant effect on plant height, number of leaves and stem diameter of coffee plant seedlings. But visually, the best treatment for plant height is NPK fertilizer with a dose of 18 grams (P2), for the number of leaves is NPK fertilizer with a dose of 22 grams (P3), and for the stem diameter all treatments are the same except for the smallest P1.